Relationship Between Self-Compassion, Emotional Quotient and Maternal Styles with Well-Being in Shiraz School Students - Alireza Zareian; Mahdi Imani (Shiraz University of Medical Sciences, 2018)
Background: According to research, ones well-being is an important factor for mental health and satisfaction in one's personal life and people with more well-being are more satisfied with their lives. Objectives: The purpose of this study is to find a relationship between self-compassion, emotional quotient, and maternal styles with the well-being in Shiraz school students. Methods: Elementary school students and high school students in the academic year of 2018 were the research population. A total of 510 students who were chosen by multistage sampling method consisted this study sample so that based on the number of schools in Shiraz, 24 primary and high schools were chosen. Two classes from each school were selected and 9 to 11 students from each class participate in study. The tools used were maternal style questionnaire, self-compassion scale (SCS), emotional quotient scale (TMMS), and subjective well being inventory (SWB). Pearson correlation coefficient and multiple regression were applied for analyzing data. Results: According to the analysis, authoritative maternal style, self-compassion, and emotional quotient were important predictors of ones well-being and they can predict 81% of well-being in this study (P = 0.003). In addition, significant correlations were found between authoritative maternal style and self-compassion (correlation coefficient = 0.88, P = 0.007), authoritative maternal style and emotional quotient (correlation coefficient = 0.86, P = 0.008), and authoritative maternal style and subjective well-being (correlation coefficient = 0.94, P = 0.005). Conclusions: According to this study, maternal style, emotional quotient, and self-compassion play an important role in the society and individuals mental health and well-being, therefore, these factors should be attended, especially the authoritative maternal style, which has the most correlation with well-being.